BMS551: Principles of Bioinformatics / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
This course is designed to equip students with the necessary theoretical knowledge and practical skills in bioinformatics. Students will be introduced to 3 major concepts in bioinformatics namely the resources, databases and tools. In resources, students will learned type of biological resources and their level of studies, background, method in human genome project and its important result to mankind. In databases students will explored type and varieties of biological databases and their unique characteristics. In tools, students will have an opportunity in analysing biological data such as sequence alignment and phylogenetic tree reconstruction